A Dual-Polarized MIMO Array Antenna System for Future Smartphone - Khalil Al-Ani, Nada M.; Shareef Al-Ani, Oras A.; Mosleh, Mahmood F.; Abd-Alhameed, Read A. (Journal of physics. Conference series, 2021)
In this paper, a dual-polarization four antennas Multiple Input Multiple Output (MIMO) scheme is proposed. The four elements are arranged over a surface area of 67×139mm 2 printed circuit board (PCB) using dielectric substrate FR-4 with epsilon 4.4 and thermal conductivity 0.025. A circular slot radiator is etched in ground plane in order to improve the radiation characteristics. To mitigate the mutual coupling in the proposed MIMO scheme, two rectangular parasitics with one open rib are embedded across square slot radiator. The proposed single antenna model covers a frequency range of 5.81-6.66 GHz at -10dB impedance bandwidth. However, the bandwidth is raised up to 1.47 MHz (5.48-6.95) GHz at -6dB. The results show that -20 dB return losses can be obtained, while -45 dB isolation was achieved for a dual microstrip line. The proposed antenna can be integrated with new smart-mobile devices for future 5G wireless communications.